2012
DOI: 10.1007/s00381-012-1789-6
|View full text |Cite
|
Sign up to set email alerts
|

Febrile seizures: an epidemiological and outcome study of 482 cases

Abstract: Children with FSs encounter a minor risk of mortality and morbidity. While recurrent seizures are observed in these children, only a minority of these patients develop epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
39
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 30 publications
9
39
1
1
Order By: Relevance
“…Dalbem JS et al 16,17 ; in the present study, this proportion was 88.8%, similar to that reported in Tunisia, Turkey, Cameroon, India, China, Iran, and England. 16---23 Status epilepticus secondary to febrile seizure was not observed in the present study, unlike the one conducted in Cameroon, which identified it in 10% of cases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Dalbem JS et al 16,17 ; in the present study, this proportion was 88.8%, similar to that reported in Tunisia, Turkey, Cameroon, India, China, Iran, and England. 16---23 Status epilepticus secondary to febrile seizure was not observed in the present study, unlike the one conducted in Cameroon, which identified it in 10% of cases.…”
Section: Discussionsupporting
confidence: 90%
“…16---23 Status epilepticus secondary to febrile seizure was not observed in the present study, unlike the one conducted in Cameroon, which identified it in 10% of cases. 24 When analyzing the frequency of febrile seizures in relation to gender, no difference was observed, similar to the research by Pavlovic et al 25 differing from some studies in which the authors described a higher frequency in the male gender, 7,16,19,26 whereas only Sillanpää et al found a predominance in the female gender. 27 The family history of febrile seizures and epilepsy in first-degree relatives was found respectively in 33.3% and 11.1% of cases.…”
Section: Discussionsupporting
confidence: 50%
“…In this study 6 cases (8.10%) had a positive family history of epilepsy, while this frequency varied from 1.6% to 9% in other studies. 10,11 In the present study, 86.4% patients had generalized seizure that is similar to the other studies. In our study, 45 patients (60.8%) were suffering from simple febrile seizure, while this was between 60 to 90 percent in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…About one-third of children with a first FS will have a recurrence. [10][11][12] Evidence that iron might be important for neurological functioning has generated considerable optimism that this element might also play a role in initiation of febrile convulsions. Previous studies examining the relationship between iron deficiency anemia and febrile convulsions have been conflicting.…”
Section: Introductionmentioning
confidence: 99%